2014
DOI: 10.5194/cp-10-359-2014
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic forcing for climate modeling: a new microphysics-based data set covering years 1600–present

Abstract: Abstract.As the understanding and representation of the impacts of volcanic eruptions on climate have improved in the last decades, uncertainties in the stratospheric aerosol forcing from large eruptions are now linked not only to visible optical depth estimates on a global scale but also to details on the size, latitude and altitude distributions of the stratospheric aerosols. Based on our understanding of these uncertainties, we propose a new model-based approach to generating a volcanic forcing for general … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 71 publications
3
116
1
Order By: Relevance
“…The magnitude of this eruption has been inferred to be at least VEI 6, with an estimated stratospheric sulfuric acid H 2 SO 4 loading of 53.74 Tg (Gao et al, 2008) and stratospheric aerosol optical depth of between 0.198 (Crowley and Unterman, 2013) and 0.27-0.28 (Crowley et al, 2008;Arfeuille et al, 2014) based on sulfate deposition recorded in ice cores. This makes the c. 1809 Unknown eruption one of the most SO 2 -rich stratospheric tropical eruptions in the last 500 years: its sulfate contribution was half that of the Tambora eruption, but almost twice that of the Mt Pinatubo eruption (VEI 6, 1991), more than two times that of the Krakatau eruption (VEI 6, 1883), and more than three times the eruptions of Agung (VEI 5, 1963) and El Chichón (VEI 5, 1982;Gao et al, 2008).…”
Section: A Guevara-murua Et Al: Observations Of a Stratospheric Aermentioning
confidence: 99%
“…The magnitude of this eruption has been inferred to be at least VEI 6, with an estimated stratospheric sulfuric acid H 2 SO 4 loading of 53.74 Tg (Gao et al, 2008) and stratospheric aerosol optical depth of between 0.198 (Crowley and Unterman, 2013) and 0.27-0.28 (Crowley et al, 2008;Arfeuille et al, 2014) based on sulfate deposition recorded in ice cores. This makes the c. 1809 Unknown eruption one of the most SO 2 -rich stratospheric tropical eruptions in the last 500 years: its sulfate contribution was half that of the Tambora eruption, but almost twice that of the Mt Pinatubo eruption (VEI 6, 1991), more than two times that of the Krakatau eruption (VEI 6, 1883), and more than three times the eruptions of Agung (VEI 5, 1963) and El Chichón (VEI 5, 1982;Gao et al, 2008).…”
Section: A Guevara-murua Et Al: Observations Of a Stratospheric Aermentioning
confidence: 99%
“…This may be related to a range of factors, including that the aerosol forcing from both Pinatubo and El Chichón is more concentrated in the Northern Hemisphere than the Southern Hemisphere in many datasets (Arfeuille et al 2014), that much of the temperature change caused by volcanoes has been suggested to occur at depth in the southern ocean (Fyfe 2006), that Antarctic sea ice has been suggested to only respond to supervolcanoes (Zanchettin et al 2014), and that Antarctic sea ice extent is less correlated with annual-mean global-mean surface air temperature than Arctic sea ice extent (Rosenblum and Eisenman 2016).…”
Section: Additional Pointsmentioning
confidence: 99%
“…We note that there are more recent volcanic reconstructions available (e.g., Sigl et al, 2015) suggesting modifications to the timing or magnitude of LM eruptions, as well as developments of data sets focusing on sulfur injection and microphysics-based evolution of the aerosol forcing (e.g., Arfeuille et al, 2014). In this contribution, we are agnostic concerning the veracity of the forcing data sets that were standard for CMIP5/PMIP3 but stress that timing of eruptions is irrelevant in our modeling context and that the model results should be interpreted as a self-consistent response to the imposed AOD and particle size.…”
Section: Datamentioning
confidence: 99%